End-systolic pressure-diameter relation of the left ventricle during transient and sustained elevations of blood pressure - Bregagnollo, Edson Antônio [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Tucci, Paulo José Ferreira [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2000)
OBJECTIVE: To assess the effect of transient and sustained variations in cardiac load on the values of the end-systolic pressure-diameter relation (ESPDR) of the left ventricle. METHODS: We studied 13 dogs under general anesthesia and autonomic blockade. Variations of cardiac loads were done by elevation of blood pressure by mechanical constriction of the aorta. Two protocols were used in each animal: gradual peaking and decreasing pressure variation, the transient arterial hypertension protocol (TAH), and a quick and 10 min sustained elevation, the sustained arterial hypertension protocol(SAH). Then, we compared the ESDR in these two situations. RESULTS: Acute elevation of arterial pressure, being it transitory or sustained, did not alter the heart frequency and increased similarly the preload and after load. However, they acted differently in end systolic pressure-diameter relation. It was greater in the SAH than TAH protocol, 21.0±7.3mmHg/mm vs. 9.2±1.2mmHg/mm (p<0.05). CONCLUSION: The left ventricular ESPDR values determined during sustained pressure elevations were higher than those found during transient pressure elevations. The time-dependent activation of myocardial contractility associated with the Frank-Starling mechanism is the major factor in inotropic stimulation during sustained elevations of blood pressure, determining an increase in the ESPDR values.
A elastância sistólica final do ventrículo esquerdo determinada durante elevações transitórias e elevações sustentadas da pressão arterial
Keywords: end-systolic pressure-diameter relations; cardiac inotropism; arterial hypertension